Bibliometric analysis: Environmental DNA (eDNA) methods in marine biodiversity research in the world and Indonesia - Banjarsari Alda Awayan; Subhan Beginer; Zamani Neviaty P.; Cahyani Ni Kadek Dita; Arafat Dondy; Ayu Inna Puspa; Lestari Dea Fauzia (BIO Web of Conferences)
The urgency to identify biodiversity and other research has made eDNA methods more popular in recent years. This article aims to provide an overview of the eDNA methods for marine biodiversity research. We used bibliometrics to analyze marine biodiversity research using eDNA methods articles in the last twenty years from 2006 to 2024 in the Scopus database. Data processing using VOSviewer and Microsoft Excel. We found that 697 articles from 2006 to 2024 were published worldwide, while Indonesia had published 22 articles and started using eDNA methods from 2019. Cross-sector and cross-country research collaboration are needed as a solution for research and management challenges and to increase competence. With the right support, eDNA can be an important tool as a solution to global environmental challenges and protect Indonesia's valuable marine biodiversity.